Factors influencing career choice of accounting students in University Putra Malaysia: qualitative pilot study - Muhamad, Haslinah; Mohd. Salleh, Mariati; Mohd Nordin, Mohd Sufri (Penerbit Akademia Baru, 2016)
The study aims to identify factors that influence career decision making among accounting students in University Putra Malaysia. The study relied on primary data obtained from the final year of accounting students, who are almost graduate. The findings reveal there were two categories based on researcher judgement, which are internal and external factors influenced the career decision making. The internal factors are interest in the subject, self- perception, relationship with family and friends as well as lecturers. The external factors stated by respondents in this study are education attainment, salary, experiences from practical training, school and university’s entry system and gender gap. All the factors, however, may related to each other and graduates have a longer time and several step to choose their career. As the study is based on a single institution, the research strategy used does not allow for wider generalisation but provides an important insight into the career decision making of accounting student in Malaysia.